Designing a Self-Care Training Package Based on Self-Efficacy for the Treatment of Patients with Multiple Sclerosis - Nemati, Mona; Rafiepoor, Amin; Moraveji , Mahtab; Sabet, Mehrdad (Mental Health and Lifestyle Journal, 2025)
This study aimed to design a self-efficacy-based self-care educational package tailored for patients with multiple sclerosis (MS) to enhance their empowerment, health literacy, treatment adherence, and psychological well-being. A qualitative research design was employed using thematic analysis based on the Attride-Stirling (2001) framework. Data were extracted from a purposive sample of scientific texts, including peer-reviewed articles, books, and theses published between 2011 and 2023 that addressed self-efficacy, empowerment, and self-care. The analysis was conducted inductively using MAXQDA software. The coding process involved identifying 236 initial codes, which were grouped into 91 basic themes, 16 organizing themes, and 6 overarching global themes. These findings informed the development of a structured 10-session educational package. Content validity of the package was confirmed through expert evaluation and calculation of the Content Validity Ratio (CVR). Thematic analysis revealed six global themes essential for MS self-care: (1) health literacy and informed decision-making, (2) physical care and healthy lifestyle, (3) mental health and stress coping, (4) social support and communication, (5) medication management and treatment adherence, and (6) spiritual education. Each session of the package addressed one or more of these domains through a combination of theoretical instruction, practical exercises, multimedia content, and group discussion. The package content was developed based on culturally relevant sources and validated theoretical constructs. The inclusion of spiritual and psychological components was emphasized to match the sociocultural needs of the target population. The developed self-care training package offers a comprehensive, theory-driven, and culturally contextualized intervention for enhancing the self-efficacy and well-being of MS patients. It integrates cognitive, behavioral, emotional, and spiritual dimensions, offering a practical and holistic approach to chronic illness management.